(untitled) (American Journal of Islam and Society, 2006)
The publication of The Private World of Ottoman Women is an important landmark in both social and gender history. Until this point, accounts of the seemingly mundane activities of Ottoman women were limited to travelers’ accounts, gossip, and information that could be discerned through the latticework guarding the imperial harem. Godfrey Goodwin’s groundbreaking work, however, introduces the reader to a society with women who were, in many areas, their husbands’ peers and, although restrained by certain gendered restrictions, had a remarkable level of mobility. His book not only removes the popular notion that “Ottoman woman” is synonymous with “harem girl,” but shows that there was an extensive network of politics, intrigue, and socio-religious change and adaptation outside of the urban elite. It also presents the reader with an understanding, although not overemphasized, that these were women who lived within the parameters of Islam as both Christian and Muslim women, and who distinctly embodied the ideals of the feminine in Islam. The book is cleverly organized to reflect both the chronology of the empire’s development and its class hierarchy. The majority of the first two chapters, “The Coming of the Nomads” and “The Wanderers,” discuss indepth the empire’s early formation and the pre-Islamic period of tribal nomadism, and essentially illustrate the empire’s boundaries and seeds of social activity. Thus they are not terribly informative about Ottoman women. But this is in no way the fault of the author, who does provide some interesting tidbits where information could be gleaned and placed into the context of the thesis ...